Georgian and Armenian Sources Concerning the Chronology of ‘Shahanshah’ title by Zakaria Mkhargrdzeli - Darchiashvili, Shanshe (Actual Problems of Kartvelology, 2025)
The author intends to remind the reader of the fact that any term referring to the ranks is due to turn into a title only after it is sanctified by legal act of the government. Until then, it remains just at the emotional level of local inhabitants. Thus, the ‘Shahanshah’ title of Zakaria Mkhargrdzeli is officially connected with the year 1199, the date when Anisi was set free and the decision was made at the Georgian royal court to reward Zakaria Mkhargrdzeli with city Anisi as well as the title of ‘Shahanshah’, previously belonging to Moslem owner.